ASPECTS OF WETTING OF HYDROPHOBIZED SURFACES TEXTURED BY A FEMTOSECOND LASER - MYRONYUK, Oleksiy; BAKLAN, Denys; GLUKHOVSKY, Vladislav (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Extractive methods of obtaining textured surfaces to ensure superhydrophobic properties must have chemical treatment. This work is aimed at determining the influence of the chemical class of modifiers (silanes, perfluorosilanes, unsaturated long-chain carboxylic acids and low molecular weight polyethylene wax) and the level of micro- and nanotexture organization on the characteristics of surface wetting. The work involved texturing of anodized aluminum with a femtosecond laser to create structures. As a result, two types of textured surfaces were obtained: with a regular microtexture in the form of columns with a square section, and a disordered fractal nanotexture with a hierarchical structure. Chemical treatment of the obtained surfaces was carried out and their effectiveness was evaluated. The study of wetting properties of surfaces was carried out by the Zisman method both with individual solvents and with the use of mixtures of solvents. As a result of the work, it is shown that the choice of the modifier of aluminum surfaces textured by a femtosecond laser plays a decisive role in determining the wetting properties, namely the values ​​of the water wetting angle and surface tension, at which the loss of stability of the Cassie state is observed. It is shown that the influence of the chemical composition of the modifier is more significant than the dimension of the texture on the surface. In particular, it is shown that in the case of using silanes and fluorosilanes, it is possible to achieve a water contact angle of 155-160° on nanotextures, while the loss of the Cassie state begins below 46-49 mN/m. When using hydrocarbon modifiers, it is possible to achieve the same high contact angles with water - 154° for oleic acid, but the stability of such surfaces is much lower - 55-65 mN/m. The difference in Cassie state stability between micro- and nanostructures was found to be within the measurement error.